Pengaruh kompensasi dan lingkungan kerja terhadap loyalitas karyawan pada PT. Jatim Jaya Perkasa Kebun Banjar Balam Indragiri Hulu - Andromike Maineldi; Susi Hendriani; Iwan Nauli Daulay (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
One of the means used to create employee loyalty to the company is compensated. Compensation is a form of payment or compensation granted to employees and arising out of employment of employees. In addition to compensation, another factor to consider is the physical working environment of the company, because it is very influential on the level of employee loyalty. This study was conducted to see the effect of compensation and the physical work environment on employee loyalty at PT. Jatim Jaya Perkasa Kebun Banjar Balam Indragiri Hulu. The population in this study were 130 employees of a day laborer remain registered in the PT. Jatim Jaya Perkasa Kebun Banjar Balam Indragiri Hulu. While the sample is taken by using Slovin formula which amounts to 98 respondents. The data was collected using a questionnaire that is then processed using multiple linear regression analysis. The results showed that the employee has a pretty good level of loyalty to the company. This is because the employees feel that the compensation they received were quite satisfactory and working environment workplace is good enough. The results of the test to get the result that compensation and working conditions simultaneously and partially significant effect on employee loyalty at PT. Jatim Jaya Perkasa Kebun Banjar Balam Indragiri Hulu with the effect of 63,5%.